88 Foundational Investigations of Tissue Dimensions and Their Relation to Captive Bolt application Sites on Cadaver Heads from Mature Swine–A Preliminary Report. (7th May 2021) - Anderson, Karly N; Baysinger, Angela; Benjamin, Madonna; Claus, James; O'Brien, Brett; Ramirez, Alejandro; Reyes, Arquimides; Vogel, Kurt D
Abstract: The objective of this study was to contrast the soft tissue thickness, cranial thickness, total tissue thickness, and cross-sectional brain area from the common frontal captive bolt placement for the captive bolt euthanasia of swine with the alternative temporal and caudal to pinna placements. One hundred and fifty-seven cadaver heads from sows and boars with estimated body weights greater than 200 kg were collected from a regional slaughter establishment following electrical stunning and assigned to the FRONTAL, TEMPORAL, or CAUDAL to pinna captive bolt placement treatments after cooling at 2–4°C for approximately 64 h. In sows, soft tissue thickness was different (P ˂ 0.0001) between the three placements (FRONTAL: 13.9±1.1 mm, TEMPORAL: 45.93±1.1 mm, CAUDAL TO PINNA: 53.8±1.1 mm), cranial thickness was different (P ˂ 0.0001) between the three placements (FRONTAL: 47.1±1.4 mm, TEMPORAL: 17.6±1.4 mm, CAUDAL TO PINNA: 30.2±1.4 mm), total tissue thickness was different (P < 0.0001) between the three placements (FRONTAL: 61.03±1.4 mm, TEMPORAL: 63.49±1.4 mm, CAUDAL TO PINNA: 84.05±1.4 mm), and cross-sectional brain area was different (P < 0.0001) between the three placements (FRONTAL: 4509.0±238.0 mm 2, TEMPORAL: 1964.4±238.0 mm 2, CAUDAL TO PINNA: 2767.5±238.0 mm 2 ). In boars, soft tissue thickness was different (P < 0.0001) between the three placements (FRONTAL: 12.9±1.7mm, TEMPORAL: 45.3±1.7 mm, CAUDAL TO PINNA: 54.7±1.7 mm), cranial thickness was different (P = 0.0193) between the FRONTAL and TEMPORAL treatments (FRONTAL: 34.8±3.2mm, TEMPORAL: 22.1±3.2 mm, CAUDAL TO PINNA: 31.7±3.2 mm), total tissue thickness was different (P < 0.0001) between the three placements (FRONTAL: 47.7±3.2 mm, TEMPORAL: 67.4±3.2 mm, CAUDAL TO PINNA: 86.4±3.2mm), and cross-sectional brain area was different (P < 0.0001) between the three placements (FRONTAL: 4031.9±153.2mm 2, TEMPORAL: 1241.8±153.2 mm 2, CAUDAL TO PINNA: 2467.5±153.2 mm 2 ). Overall, the preliminary data indicated that the FRONTAL placement appears to have the greatest likelihood for successful euthanasia and may present less risk than the alternative TEMPORAL or CAUDAL TO PINNA placements.